1978
DOI: 10.7601/mez.29.325
|View full text |Cite
|
Sign up to set email alerts
|

A control experiment with chemosterilized male Culex pipiens fatigans Wied. in a village near Delhi surrounded by a breeding-free zone

Abstract: A control experiment with chemosterilized male Cutex pipiens fatigans Wied. in a village near Delhi surrounded by a breedmg-free zone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…The bulk of the failures seem to be due to faulty planning, execution and surveillance of operations. Thus it becomes essential to strengthen the already existing cadre of mosquito control workers (MACDONALD, 1978) and to carry out cost/ benefit studies for the control operations on the basis laid down by CVJETANOVIC and GRAB (1976) to ensure better utilization of the available funds. Perhaps, it would then be possible to maintain C. p. quinquefasciatus densities at a sufficiently low level to ensure that the mosquito ceases to be one of the major health problems in the human environment in the tropics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the failures seem to be due to faulty planning, execution and surveillance of operations. Thus it becomes essential to strengthen the already existing cadre of mosquito control workers (MACDONALD, 1978) and to carry out cost/ benefit studies for the control operations on the basis laid down by CVJETANOVIC and GRAB (1976) to ensure better utilization of the available funds. Perhaps, it would then be possible to maintain C. p. quinquefasciatus densities at a sufficiently low level to ensure that the mosquito ceases to be one of the major health problems in the human environment in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials carried out in the Delhi region (YASUNO et al, 1978;BROOKS et al, 1976), the first using chemosterilized males and the second using males incompatible with the local strains and in which a sexlinked translocation had been introduced, resulted in a high percentage of sterility. However, in both cases the trials did not have the success anticipated because of reinvasion of mosquitoes from the outside.…”
Section: Choice Of Pesticides While C P Quinquefasciatusmentioning
confidence: 97%
“…were conducted by the WHO/ICMR unit in New Delhi, [20] although infiltration of surrounding fertile females limited efficacy of the trial. [21] Preliminary trials of thiotepa-sterilized Aedes aegypti were also conducted alongside radiation and genetic methods. [22] …”
Section: Laboratory and Field Trials Of Aziridine-phosphoryl Chemomentioning
confidence: 99%
“…A second treatment of an adulticide, pyrethrum, was applied to one set of villages. Although the Delhi programmes, summarized by Pal (1974), Yasuno et al (1976) and Curtis (1977), were not permitted to continue to the stage of measuring population suppression, the programmes proposed in these tests included population monitoring and integration of adult and larval control. A more recent review of the potential for mosquito control (Curtis and Andreasen 2000) cited the importance of barriers to immigration of females into treated areas.…”
Section: Direct Insecticide Application For Adult Population Suppressionmentioning
confidence: 99%
“…After several attempts to introduce sterility into the populations (reported from 1971 and 1972 tests with negative results), tests were designed to distinguish the effects of rearing, chemosterilization and strain genetics from the effects of strain contamination with females and immigration (Pal andLaChance 1974, Pal 1974). Yasuno et al (1976) reported the results of a 5-month sterile insect release (February to July 1973) of chemosterilized males into an area with mosquito fish Gambusia affinis (Baird and Girard) or larvicide-treated (temephos) breeding sites in buffer zones. A second treatment of an adulticide, pyrethrum, was applied to one set of villages.…”
Section: Direct Insecticide Application For Adult Population Suppressionmentioning
confidence: 99%